THE CIVIL RESPONSIBILITY OF THE DIGITAL INFLUENCER AND THE CONSUMER'S VULNERABILITY BEFORE SOCIAL NETWORKS: . (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
Since the beginning of human life, man has been inspired by his fellow men to act, survive and even to structure his personality, tastes and preferences. It is natural that we always seek to cling to a "leader", someone who will inspire us and dictate the paths we must take. With the evolution of the species, we obtained new technologies, the internet has become something fundamental in our daily life, in such a way that it reflects in the most diverse variables of human relations and its absence can cause immeasurable damage since in the current world, practically the functioning everything is conditioned to electronic devices and the internet. Based on this reality, not only has technology changed, but new opportunities have also emerged from it. Today, it is very common to hear about “digital influencer”, “blogger”, or “content creator”, which are the people who share their routine on social networks, tips, and advertise products to the public that accompanies them. However, this activity happened in such a proportion that it causes today in several controversial and critical points of view, since it is a recent activity that does not have so many regulations and it becomes a great challenge to control the information disseminated on social media. Thus, the purpose of this article is to explain about the concept of digital influencer in consumer relations, mentioning his responsibility to the internet public.